The Involvement of Glycerophospholipids in Susceptibility of Maize to Gibberella Root Rot Revealed by Comparative Metabolomics and Mass Spectrometry Imaging Joint Analysis - Qing Wang; Zi’an Zhao; Xin Li; Xiquan Gao (Plants)
Gibberella root rot (GRR), caused by Fusarium graminearum, is one of the major threats to maize production. However, the mechanism underlying maize’s response to GRR is not fully understood. Multi-omics study incorporating metabolomics reveals insights into maize–pathogen interactions. Using metabolomics and mass spectrometry imaging (MSI), maize inbred lines with GRR resistance (W438) and susceptibility (335M) were deployed to characterize specific metabolites associated with GRR. Analysis of significantly altered metabolites suggested that glycerophospholipid metabolism was highly associated with GRR resistance or susceptibility. Furthermore, the distinct accumulation of lysophosphatidylethanolamine (lysoPE) and lysophosphatidylcholine (lysoPC) from glycerophospholipid metabolism, along with the significant up-regulation of phospholipase (PLA) gene in the susceptible line, suggested that high levels of lysoPC and lysoPE contributed to GRR susceptibility. Meanwhile, genes encoding lysophospholipase (LPLA), the detoxification enzymes of lysoPC, were significantly activated in both genotypes. However, the significantly higher expression of LPLAs in the resistant line corresponded to a significant increase in the content of non-toxic sn-glycero-3-phosphocholine, whereas this increase was not observed in the susceptible line. MSI analysis revealed the involvement of other potential phospholipids in GRR susceptibility. Taken together, maintaining an appropriate concentration of lysophospholipids is crucial for their role in the signaling pathway that triggers GRR resistance without causing damage to maize roots.